The cost of sleeping sickness vector control in Yasa Bonga, a health district in the Democratic Republic of the Congo. - Rian Snijders; Alexandra P M Shaw; Richard Selby; Inaki Tirados; Paul R Bessell; Alain Fukinsia; Erick Miaka; Fabrizio Tediosi; Epco Hasker; Marina Antillon (PLoS Neglected Tropical Diseases)
Gambiense human African trypanosomiasis (gHAT), a neglected tropical disease caused by a parasite transmitted by tsetse flies, once inflicted over 30,000 annual cases and resulted in an estimated half a million deaths in the late twentieth century. An international gHAT control program has reduced cases to under 1,000 annually, encouraging the World Health Organization to target the elimination of gHAT transmission by 2030. This requires adopting innovative disease control approaches in foci where transmission persists. Since the last decade, case detection and treatment, the mainstay of controlling the disease, is supplemented by vector control using Tiny Targets, small insecticide-treated screens, which attract and kill tsetse. The advantages of Tiny Targets lie in their relatively low cost, easy deployment, and effectiveness. The Democratic Republic of Congo (DRC), bearing 65% of the 799 gHAT cases reported globally in 2022, introduced Tiny Targets in 2015. This study estimates the annual cost of vector control using Tiny Targets in the health district of Yasa Bonga in the DRC and identifies the main cost drivers. Economic and financial costs, collected from the provider's perspective, were used to estimate the average cost of tsetse control expressed as cost (i) per target used, (ii) per target deployed, (iii) per linear kilometre of river controlled, and (iv) per square kilometre protected by vector control. Sensitivity analyses were conducted on key parameters for results robustness. The estimated annual economic cost for protecting an area of 1,925 km2 was 120,000 USD. This translates to 5.30 USD per target used each year, 11 USD per target deployed in the field, 573 USD per linear km treated, and 62 USD per km2 protected. These costs in the DRC are comparable to those in other countries. The study provides valuable information for practitioners and policymakers making rational, evidence-based decisions to control gHAT.